2021
DOI: 10.1210/clinem/dgab062
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Prepubertal Onset of Type 1 Diabetes and Age of Menarche on Polycystic Ovary Syndrome Diagnosis

Abstract: Context Higher prevalence of polycystic ovary syndrome (PCOS) in women with type 1 diabetes (T1DM) is linked to exogenous insulin, especially when diabetes is diagnosed before puberty. Objective The study evaluates the impact of prepubertal onset of T1DM and insulin therapy on PCOS diagnosis and phenotypic characteristics in women with T1DM. Design, Setting and Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 19 publications
1
16
1
Order By: Relevance
“…The associations of AAM and the prevalence of PCOS have been previously explored. Sadrzadeh et al 9 found that patients diagnosed with PCOS had a significantly older AAM (15–18 years) (odds ratio [OR], 3.31 [95% CI, 2.18–5.04]), while a recent study showed that patients with type 1 diabetes on insulin treatment might be more susceptible to PCOS development, especially when their pubertal age onset was at 8 to 11 years, dominantly younger than their peers 10 …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The associations of AAM and the prevalence of PCOS have been previously explored. Sadrzadeh et al 9 found that patients diagnosed with PCOS had a significantly older AAM (15–18 years) (odds ratio [OR], 3.31 [95% CI, 2.18–5.04]), while a recent study showed that patients with type 1 diabetes on insulin treatment might be more susceptible to PCOS development, especially when their pubertal age onset was at 8 to 11 years, dominantly younger than their peers 10 …”
Section: Introductionmentioning
confidence: 99%
“…10 However, consensus still has not been reached regarding how AAM impacts the risk of PCOS. 9,10 In addition, the majority of published papers are epidemiologic and case-controlled studies, which are naturally with limitations in the causality clarification due to blurred temporal orders. In addition, it has been noted that published observational studies have failed to roll out violations from confounding risk factors, which might affect the confidence in conclusions to some extent.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This leads to an inevitable therapeutic increase in the dose of insulin therapy, resulting in exogenous systemic hyperinsulinemia, which stimulates androgen over-synthesis and secretion in the ovaries and adrenal glands, which in turn may lead to the development of PCOS [ 16 ]. However, comparing different insulin treatment modalities did not reveal differences in the prevalence of PCOS and its symptoms [ 17 ]. In addition, comparisons between well-controlled and poorly controlled adolescents with T1D did not reveal differences in androgen concentrations and ovarian parameters [ 17 ].…”
Section: Introductionmentioning
confidence: 99%